The Correlation Between Menstrual Cycle with Anemia Among Female Adolescents at SMA Negeri 1 Meukek, South Aceh - Yaumul Nuzullifa; Fadjri, T.Khairul (JAND: Journal of Applied Nutrition and Dietetic, 2025)
Anemia is a condition characterized by a reduction in the number or size of red blood cells or a decrease in hemoglobin (Hb) concentration below normal levels. The menstrual cycle is measured by the interval between the first day of one menstruation and the first day of the next. Body Mass Index (BMI) is an anthropometric indicator used to assess nutritional status, particularly in individuals over the age of 18.This study aimed to examine the correlation between menstrual cycle patterns and Body Mass Index (BMI) with the incidence of anemia among female adolescents at SMA Negeri 1 Meukek, South Aceh. This was an analytical survey study with a cross-sectional design. A total of 113 students from SMA Negeri 1 Meukek served as the population, and 53 students were selected as the sample using the Slovin formula and random sampling. Data were collected using a questionnaire, a microtoise for height measurement, a digital scale for weight, and the Easy Touch GCHb 3-in-1 device to measure hemoglobin levels. Bivariate analysis was conducted to assess associations. The analysis showed no significant correlation between BMI and the incidence of anemia (p = 0.213 > α = 0.05), indicating that BMI is not associated with anemia in this population. However, a significant correlation was found between menstrual cycle irregularities and anemia (p = 0.004 < α = 0.05). Based on these findings, it is recommended that schools and health authorities increase awareness and education on menstrual health and anemia prevention among adolescent girls.